The Effect Of Economic Growth, Government Expenditure And Special Allocation Funds On Poverty In West Lombok District - Hayati, Atiyah Nurul; Abdul Manan; Siti Fatimah (LPPM Institut Studi Islam Sunan Doe, 2024)
This research aims to examine how the effect of economic growth, government expenditure and special allocation funds on poverty in West Lombok District. This research uses associative quantitative research types and data collection techniques used in the form of documentation techniques with data sources, namely in the form of detailed financial report data for West Lombok Regency which has been published by the Regional Financial and Asset Management Agency and data from the Central Bureau of Statistics West Lombok Regency in 2012-2021. The data analysis procedure used to test the hypothesis is through the SPSS 23 application with partial and simultaneous tests. The results showed that (1) Economic Growth had a significant and positive effect on poverty in West Lombok Regency in 2012-2021; (2) Government Expenditure did not have a significant and negative effect on poverty in West Lombok District in 2012-2021; (3) The Special Allocation Fund did not have a significant and positive effect on poverty in West Lombok District in 2012-2021; (4) economic growth, government spending and special allocation funds together have no significant effect on poverty in West Lombok District in 2012-2021.